Implementation of a psychodermatology clinic at a major health system in Detroit - L. Seale, BS; J.V. Gaulding, MD; D. Porto, MD; D. Prabhakar, MD, MPH; H. Kerr, MD (Wolters Kluwer, 2018)
The association between psychiatric and dermatologic disorders has been well characterized in the present literature with estimates of up to 40% of dermatology patients having concomitant psychiatric problems that are often related to their skin condition. Here, we present our experience regarding the implementation of a psychodermatology clinic in Detroit, Michigan. The most commonly referred conditions were delusions of parasitosis, neurotic excoriations, and isotretinoin initiation for patients with a history of psychiatric conditions. Seventy-three percent of referred patients were female. By creating a monthly clinic for patients who are diagnosed with skin conditions and associated psychiatric disorders or psychological symptoms, we are able to meet the needs of these patients with a synergistic relationship between health care providers.